DIAGNOSIS WITH TYPE 2 DIABETES AND CHANGES IN PHYSICAL ACTIVITY AMONG MIDDLE-AGED AND OLDER ADULTS IN THE U.S. (11th November 2018) - Nicklett, E; Chen, J; Xiang, X; Sonnega, A; Abrams, L; Johnson, K; Assari, S
Abstract: Physical activity (PA) is an effective strategy for diabetes management and is central to the diabetes regimen. However, many older adults with type 2 diabetes (DM2) do not engage in regular PA. This is the first study to examine diagnosis-related transitions in PA among a population-based sample of middle-aged and older-adults in the U.S. We examined associations between PA changes and DM2 diagnosis among 2, 394 participants aged 51+ in the Health and Retirement Study diagnosed with DM2 between 2006–14. PA was measured with metabolic equivalents of task (MET) estimated values accounting for vigor and frequency of self-reported PA. Piecewise mixed models were centered at diagnosis to examine changes in MET values and rate of decline in METs over time. We then tested whether these changes differed by age at diagnosis, race/ethnicity, gender, or education. PA declined as participants aged. DM2 diagnosis was followed by a significant increase in METs (0.50 MET, SE: 0.20, p<0.05), suggesting diagnosis-related increases in PA. Following diagnosis, the rate of PA decline steepened slightly but the change in slope was not significant. PA declines after diagnosis were significantly moderated by age and by race/ethnicity, with more pronounced declines among participants diagnosed at a relatively older age and by non-Hispanic white participants compared to African American, Hispanic/Latino, and other participants. Future research in this area should examine the underlying reasons for changes in PA behaviors in response to diagnosis events to inform clinical and community intervention strategies to improve disease-related outcomes of older adults over time.